Assessing the inundation risk resulting from extreme water levels under sea-level rise: a case study of Rongcheng, China. Issue 1 (1st January 2018) - Feng, Aiqing; Gao, Jiangbo; Wu, Shaohong; Liu, Lulu; Li, Yanzhong; Yue, Xiliu
ABSTRACT: Driven by global climate change, sea-level rise would exacerbate the hazard of extreme water level as a disaster-inducing factor. Based on Representative Concentration Pathway (RCP) 2.6, 4.5, and 8.5, this study explored the inundation risk of extreme water levels under climate change and Rongcheng was a case study. Pearson Type III (P-III) distribution was used for refitting recurrence periods of extreme water level. Expected losses exposed to extreme water levels were assessed through inundated area and depth per-unit loss values and vulnerability curves of land-use types. Results indicated that sea-level rise significantly shortened recurrence period in 2050 and 2100, which suggested a higher frequency of extreme water level in future. A large increase in expected direct losses would reach an average of 60% with a 0.82-m sea-level rise (under RCP 8.5) in 2100. Moreover, affected population and gross domestic product would grow 4.95% to 13.87% and 3.66% to 10.95% in 2050, respectively, while the increment in 2100 would be twice. Residential land and farmland were demonstrated as at greater inundation risk because of higher exposure and losses. Consequently, the intensifying hazard and the increase in possible losses suggested that sea-level rise would exacerbate future inundation risk in coastal region.